ANALISIS PENGARUH PARTISIPASI PEREMPUAN TERHADAP PERTUMBUHAN EKONOMI DI SUMATERA UTARA TAHUN 2017-2021: ANALYSIS OF THE EFFECT OF WOMEN'S PARTICIPATION ON ECONOMIC GROWTH IN NORTH SUMATRA 2017-2021 - Lulu. S, Ratih Yunita (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Timor, 2023)
Economic growth is very important in economic development, which is interpreted as one measure of the success of a country's economy. An economy is said to experience change if the level of economic activity is higher than that achieved from the previous period. In addition, the empowerment of human resources will also have an impact on the economic conditions of a region. Fulfillment of basic human rights, women and men have the same degree and rights. This study aims to analyze the effect of Women's Education (X1), and Women's Participation as Professional Workforce (X2), on Economic Growth (Y) in North Sumatra. This type of research uses quantitative descriptive research. The data processed is published data from the Central Bureau of Statistics in the form of Women's School Participation Rates, Women's Participation Rates as Professional Workers, and GRDP for 2017-2021. The analytical method used in this study is the panel data regression method. Meanwhile, hypothesis testing uses the F test to test variables simultaneously, the T test to test variables partially with a significance level <0.05, and the Coefficient of Determination (R2) to explain how much the proportion of variation in the independent variables can explain the dependent variable. From the test results in this study it is known that partially Women's Education has a positive and significant influence, Women as Professional Workforce has a negative and insignificant effect. Meanwhile, simultaneously the education of women and women as professional workers has a significant influence on economic growth in North Sumatra.